2013
DOI: 10.1093/ejcts/ezt388
|View full text |Cite
|
Sign up to set email alerts
|

A novel composite coronary bypass graft strategy: the saphenous vein bridge—a pilot study

Abstract: Revascularization of the anterolateral territory using the LIMA-SVB is a promising approach considering its clinical safety and favourable patency rate results. A prospective randomized clinical trial is underway to compare this technique to conventional CABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Based on our experience [10], 2.15 grafts on average are required on the anterolateral territory (that is, for about 15% of patients >2 grafts will be performed on the anterolateral territory). We can estimate the graft patency index for all anterolateral grafts in the conventional group with separate LIMA-LAD and SVG to anterolateral coronary targets at ((96% + (1.15 x 85%))/2.15) = 90%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our experience [10], 2.15 grafts on average are required on the anterolateral territory (that is, for about 15% of patients >2 grafts will be performed on the anterolateral territory). We can estimate the graft patency index for all anterolateral grafts in the conventional group with separate LIMA-LAD and SVG to anterolateral coronary targets at ((96% + (1.15 x 85%))/2.15) = 90%.…”
Section: Methodsmentioning
confidence: 99%
“…In a pilot study with 256 patients (mean follow-up of 3 years), we demonstrated the feasibility and security of the new CABG technique [10]. Incidences of clinical events (mortality, myocardial infarction (MI), low cardiac output syndrome, re-exploration for bleeding and recurrence of angina) over the short and long term were low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients (n=40) were prospectively selected to undergo CT angiography in the context of two other studies (11,12).…”
Section: Study Populationmentioning
confidence: 99%
“…The LIMA is grafted on the hood of the SVB, usually immediately above the LAD anastomosis, to ensure an "almost" direct LIMA-LAD anastomosis, while also providing flow to the other arteries of the anterolateral territory through the SVB ( Figure 2). Clinical follow-up showed this technique to be feasible and safe (10). Preliminary results of conventional or CT angiographic follow-up have shown that, when present, graft dysfunction (stenosis or occlusion) of the composite LIMA-SVB graft is usually limited to the A C C E P T E D M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%